Fire testing and design of slender stainless steel I-sections in weak-axis flexure - Xing, Zhe (2022)
The structural fire response of slender austenitic stainless steel I-sections in weak-axis flexure is studied experimentally for the first time. The presented experimental programme comprised local geometric imperfection measurements for all the test beams, room temperature material tests, a reference room temperature weak-axis bending test and a series of elevated temperature weak-axis bending tests. The experimental setup, procedure and measured responses of the test specimens are fully described. The results demonstrate that, despite the studied cross-section being slender, considerable inelastic strength reserves were displayed. Such behaviour has previously been observed in steel I-sections in weak-axis flexure at room temperature. The test results are used to assess the accuracy of existing fire design provisions in predicting the weak-axis bending moment resistances of slender stainless steel I-sections. Significantly improved capacity predictions were achieved through the application of a plastic effective width method in which the beneficial influence of the partial spread of plasticity is captured.